The Role of Government Public Relations (Humas Pemerintah) in Establishing a Positive Government Reputation at the South Sulawesi Provincial Governor's Office - Muhammad Faisal Jufry (Pustaka Digital Indonesia, 2023)
This research aims to explore and understand the role played by Government Public Relations (Humas Pemerintah) in shaping a positive reputation for the government at the South Sulawesi Provincial Governor's Office. With the rapid development of communication and information, Government Public Relations plays a crucial role in building the image and relationships between the local government and the community. Government Public Relations is tasked with communicating government policies, programs, and achievements to the public. They must also address various communication challenges that may arise during governance, such as sensitive issues or crises. In this context, the role of Government Public Relations is vital to ensure that the information conveyed is accurate, transparent, and comprehensible to the public. Furthermore, Government Public Relations must work diligently to build public trust in the government. This can be achieved through open communication, responsiveness to feedback and concerns from the public, and involving the community in decision-making processes. By doing so, the positive reputation of the government can be strengthened and maintained. This research will delve deeper into the strategies and practices of Government Public Relations at the South Sulawesi Provincial Governor's Office in achieving these objectives. The results of this study are expected to provide valuable insights into the role of Government Public Relations in shaping a positive government image, not only at the regional level but also as a model for governments throughout Indonesia.